Uso de solventes verdes na obtenção de extratos de bagaço de mirtilo para uso como corante em sorvete de base láctea - Bianchessi, Suzane (2023)
Green chemistry, also known as sustainable chemistry, represents an innovative approach aimed at developing chemical processes and products that are both economically viable and environmentally friendly. Numerous sustainable solvents have demonstrated efficiency in extracting anthocyanic compounds. Beyond their coloring capabilities, these solvents also exhibit significant biocompatibility and bioactivity. However, few studies have explored the direct application of these extracts in foods, whether as natural colorants or sources of bioactive compounds.Dairy-based ice creams, being widely consumed products, present an ideal model for investigating the direct application of anthocyanin-rich extracts, considering frozen storage and the presence of whey proteins that can bind to and stabilize these pigments. Waste from fruit processing industries, such as blueberry pomace, offers economically appealing alternative sources for anthocyanin extraction. The objective of this study was to assess the utilization of blueberry pomace extracts (BE) obtained with sustainable solvents as colorants in dairy-based ice cream, comparing them with conventionally obtained extracts (organic solvent). The sustainable blueberry pomace extracts produced were: NADES-BE, a natural deep eutectic solvent (NADES) composed of choline chloride:glycerol:citric acid in a ratio of 0.5:2.0:0.5 (molar ratio), and AqueousCA-BE, an aqueous solution containing 1% citric acid. Conventional organic solvent extraction (OS-BE) used methanol (removed before ice cream use). All blueberry extracts were adjusted for concentration to enable the addition of the same mass of anthocyanins, irrespective of the extract type. The dairy-based ice cream was prepared using a standard formulation, and the following formulations were created: I) control formulation; II) color control formulation (with artificial dye); III) NADES-BE formulation; IV) AqueousCA-BE formulation; V) OS-BE formulation. The ice creams were analyzed for their physical, chemical, nutritional and sensory characteristics. The NADES-BE ice cream (pH 5.78) exhibited a stable pink color (a* 19.09; C* 19.17, h* 354.87) and a lower melting rate (70% lower) than other formulations. However, it was associated with acidic, bitter, astringent, and unpleasant flavors, resulting in the lowest overall acceptance among the formulations. Conversely, the AqueousCA-BE ice cream displayed a pale purple color (pH 6.31; a* 2.27; C* 2.31, h* 354.02), with technological and sensory performance similar to that of OS-BE (pH 6.48; a* 1.31, C* 2.00, h* 314.22). Regardless of the solvent used, anthocyanin-based extracts from blueberry pomace provided a consistently stable color to milk-based ice cream stored at temperatures equal to or below -15°C for up to 35 days. These findings suggest the feasibility of obtaining ready-to-use anthocyanin-rich extracts from sustainable solvents, particularly the aqueous extract of citric acid, for use as colorants in milk-based ice cream formulations.